Dentalion (Hymenoptera: Eulophidae: Entedoninae) a new genus from tropical America with eleven new species - Hansson, Christer (Zootaxa, 2011)
Dentalion gen. nov. (Hymenoptera: Eulophidae: Entedoninae), is described from the northern part of the Neotropical region, from Costa Rica to Ecuador and Brazil, and the Caribbean (Trinidad & Tobago). It comprises eleven new species: D. alveum, D. ambonatum, D. apertum, D. apon, D. crassicornis, D. jimenezi, D. mischum, D. noyesi, D. pinguicornis, D. pnigaliae, D. quadrifer. These species are diagnosed, described and illustrated, and a key for their identification is provided. Dentalion is characterized by two putative autapomorphies and two synapomorphies. The phylogenetic implications of these apomorphies are discussed briefly.